PENDAMPINGAN EDUKASI SEJARAH MINANGKABAU UNTUK MOTIVASI BELAJAR MAHASISWA - Nora Afnita; Martin Kustati; Rezki Amelia; Joni Indra Wandi (Universitas Muhammadiyah Mataram, 2025)
Abstrak: Motivasi belajar mahasiswa sering mengalami penurunan akibat kurangnya keterkaitan antara materi akademik dengan budaya local. Pendampingan ini bertujuan untuk meningkatkan soft skills dan hard skill mahasiswa, seperti kepemimpinan, komunikasi, dan kerja sama, serta memperkenalkan nilai-nilai budaya yang dapat diterapkan dalam kehidupan akademik dan profesional mereka. melalui kajian sejarah Minangkabau dengan metode Asset-Based Community Development (ABCD) dengan tahapan sosialisasi, penyuluhan, (workshop interaktif praktikum eksploratif. Kegiatan ini melibatkan 30 mahasiswa IAI Sumbar sebagai Mitra pendampingan. Metode yang digunakan meliputi sosialisasi, penyuluhan, workshop, dan praktikum yang membahas nilai-nilai sejarah dan filosofi Minangkabau. Hasil pendampingan menunjukkan peningkatan motivasi belajar sebesar 40% dan peningkatan soft skills seperti kepemimpinan dan komunikasi sebesar 35% melalui Simulasi/Role-Play. Selain itu, terdapat peningkatan nilai ekonomis sebesar 25% bagi mahasiswa yang mengembangkan produk edukatif berbasis sejarah Minangkabau. Adapun solusi yang ditawarkan dalam kegiatan ini adalah dengan memberikan motivasi tambahan melalui diskusi interaktif dan merancang kunjungan lebih efisien agar dapat mengakomodasi lebih banyak peserta.Abstract: This mentoring aims to improve students' soft skills, such as leadership, communication, and cooperation, as well as introduce cultural values that can be applied in their academic and professional lives. through the study of Minangkabau history with the Asset-Based Community Development (ABCD) method with stages (1) socialization (2) counseling, (3) interactive workshops (4) explorative practicum, Student learning motivation often decreases due to the lack of connection between academic material and local culture. To overcome this problem, this activity involved 30 IAI West Sumatera students as mentoring subjects. The methods used include socialization, counseling, workshops, and practicums that discuss Minangkabau historical and philosophical values. The results showed an increase in learning motivation by 40% and an increase in soft skills such as leadership and communication by 35%. In addition, there is an increase in economic value by 25% for students who develop educational products based on Minangkabau history. Thus, the solution offered in this assistance is a series of activities that integrate Minangkabau history in student learning. The designed program includes: (1) socialization on the importance of Minangkabau history in education, (2) counseling on the values of leadership and work ethic contained in Minangkabau history, (3) interactive workshops involving students, (4) workshops on the importance of Minangkabau history in education.